Investigation of appointment booking strategies at specialty clinics - Ang Jun, James (2018)
Appointment booking systems around the world have been designed to reduce the amount of bottlenecking in appointments within healthcare providers, thus maximising the efficiency of delivering treatment to its patients and improving their productivity. Prior to the study, improvements were already made to the appointment booking systems of an eye care specialty clinic to reduce the amount of waiting time for the patients. In this project, we will investigate the effectiveness of these strategies that were implemented using simulation modelling. In this study, it was shown that having the doctor arrive earlier at the clinic reduce the amount of time patients have to spend at the clinic tremendously. Also, assigning patients who visited specialty clinics for their first time to come in the morning rather than spread throughout the day help to ease the flow of patients and reduce the amount of time patients spend waiting in the clinic for their treatment.